(untitled) (Research, Society and Development, 2022)
With the emergence of COVID-19, mental health problems such as anxiety and depression have become even more frequent among society, as well as the use of psychotropic drugs such as anxiolytics and antidepressants. The objective of the study is to carry out an integrative review on the consumption of anxiolytics and antidepressants during the COVID-19 pandemic, based on epidemiological surveys made available in the scientific community. The study was conducted through an integrative review, using previously defined descriptors in different databases. Inclusion and exclusion criteria were applied for the selection of works closely related to the theme. Comparative analyzes were identified between a previous period and during the pandemic, which allowed verifying the evolution in the use and/or dispensing of medicines used for the treatment of disorders such as anxiety and depression. It was observed that a higher frequency of use may vary according to the place and/or region analyzed, although there are common points in the studies, when a greater occurrence of use of drugs of the benzodiazepine and inhibitor classes is reported selective serotonin reuptake. From the survey carried out, it was possible to identify the main drugs and their respective pharmacological classes used in the treatment of cases of anxiety and depression during the pandemic, with emphasis on a high consumption of clanazepam, sertraline and amitriptyline.